2015
DOI: 10.1007/s10928-015-9436-y
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and validation of enzyme and transporter off-targets for metformin

Abstract: Metformin, an established first-line treatment for patients with type 2 diabetes, has been associated with gastrointestinal (GI) adverse effects that limit its use. Histamine and serotonin have potent effects on the GI tract. The effects of metformin on histamine and serotonin uptake were evaluated in cell lines overexpressing several amine transporters (OCT1, OCT3 and SERT). Metformin inhibited histamine and serotonin uptake by OCT1, OCT3 and SERT in a dose-dependent manner, with OCT1-mediated amine uptake be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 78 publications
(92 reference statements)
0
40
0
Order By: Relevance
“…Duodenal biopsy study on metformin-naive individuals found that metformin stimulated the release of serotonin (5-HT) from enterochromaffin cells [28]; however, this effect is not through the 5-HT3 receptor, as the response is not altered if receptor is inhibited. Alternatively it could be explained that, the uptake of metformin via SERT or Organic Cation Transporter (OCT1) results in decreased transport of serotonin and results in GI side-effects [29].…”
Section: Mechanism Of Metformin Induced Gastrointestinal Side Effectsmentioning
confidence: 99%
“…Duodenal biopsy study on metformin-naive individuals found that metformin stimulated the release of serotonin (5-HT) from enterochromaffin cells [28]; however, this effect is not through the 5-HT3 receptor, as the response is not altered if receptor is inhibited. Alternatively it could be explained that, the uptake of metformin via SERT or Organic Cation Transporter (OCT1) results in decreased transport of serotonin and results in GI side-effects [29].…”
Section: Mechanism Of Metformin Induced Gastrointestinal Side Effectsmentioning
confidence: 99%
“…Despite its clinical importance, the underlying pathophysiology of metformin intolerance is not yet clear. However multiple possible hypotheses have been proposed including high intestinal metformin concentration (3,4), its effect on the gut microbiota (5), altered transportation of serotonin or direct serotonergic effects (6), and reduced ileal absorption of bile acid salts (7).…”
Section: Introductionmentioning
confidence: 99%
“…We explored which combinations of conformer generation and E3FP parameters produced the most effective 3D fingerprints for the task of recovering correct ligand binders for over 2,000 protein targets using the Similarity Ensemble Approach (SEA). SEA compares sets of fingerprints against each other using Tanimoto coefficients (TC) and determines a p-value for the similarity among the two sets; it has been used to predict drug off-targets 4,5,37,38 , small molecule mechanisms of action [39][40][41] , and adverse drug reactions 4,42,43 . For the training library, we assembled a dataset of small molecule ligands that bind to at least one of the targets from the ChEMBL database with an IC 50 of 10 μM or better.…”
Section: Sea 3d Fingerprint Performance Exceeds That Of 2d In Bindingmentioning
confidence: 99%